THE GEOCHEMICAL CHARACTERISTICS AND TECTONIC-MAGMATIC IMPLICATIONS OF THE LATEST-PALEOZOIC VOLCANIC ROCKS FROM SANTANGHU BASIN, EASTERN XINJIANG, NORTHWEST CHINA - Zhao Z.H.; Wang Y.; Guo Z.J.; Han B.F. (My University, 2006)
The major element, trace element and isotopic data of the latest-Paleozoic volcanic rocks which include early-Carboniferous andesites (ECA), early-Permian trachytoids (EPT) and middle-Permian basalts(MPB), from Santanghu basin, Eastern Xinjiang, NW China, are reported in this paper. The majority of samples have enriched large ion lithophile elements (LILE) relative to high field strength elements (HFSE), strongly negative anomalies in Ta and Nb relative to rare earth element (REE), enriched light rare earth element (LREE) relative to heavy rare earth element (HREE), as a typical characteristics of subduction-related magmas. Additionally, ECA have high Zr/Nb (4.67 - 12.39), low Nb/La ratios (0.27 - 0.30), Ce/Ce* = 0.63 - 0.89, Sr/Sr* = 1.32 - 2.49, negative anomalies in Ti, (87Sr/86Sr)i = 0.70408 - 0.70451 and εNd (t) = + 7. 42 - + 7.88. In contrast with ECA, EPT are characterized by higher LILE concentrations and more negative anomalies in Ti and P, especially, by Ce/Ce* = 0.72 - 1.64, Sr/Sr* = 0.38 - 1.87, and relatively low Al2O3 and CaO, and by (87Sr/86Sr)i = 0.70414 - 0.70481 and εNd (t) = + 4. 93 - + 6.13 distinguished from ECA. MPB have distinct characteristics with low LILE concentrations, higher Nb and Ta concentrations, Ce/Ce* = 0.69 - 0.84, Sr/Sr* = 1.44 - 2.13, no negative anomalies in Ti, and with (87Sr/86Sr)i = 0.70388 - 0.70396 and εNd (t) = + 7.10 - + 7.99 from ECA. All the geochemical characteristics of latest-Paleozoic volcanic rocks from Santanghu Basin indicate ECA were typical of subduction-related magmas and shared a convergent margin setting in early Carboniferous or earlier, and magmas were generated by partial melting of the depleted mantle wedge modified by sediments or fluids. After late Carboniferous, Santanghu basin was under collapse setting of post-collision and shared extensional tectonic setting. EPT and MPB were all anorogenic volcanic rocks. The generation of EPT magmas origined from melting of orogenic components prior to early Permian underplated by upwelling of new asthenospheric mantle and the magmas of MPB derived from partial melting of asthenospheric mantle and were contaminated by orogenic components prior to Permian. Conclusionally, the dynamic model of stretch and extension in Permian in Santanghu basin was a result from interaction between upwelling of partial melting asthenospheric mantle induced by delamination of thickened subcontinental mantle root and orogenic components or juvenile crust formed before Permian with low (87Sr/86Sr)i and positive εNd (t). All the geochemical characteristics of latest-Paleozoic volcanic rocks also indicate they have no obvious characteristics related to mantle plume.
Keywords: GEOCHEMICAL CHARACTERISTICS; LATEST-PALEOZOIC; SANTANGHU BASIN; TECTONIC-MAGMATIC EVOLUTION; VOLCANIC ROCKS; Палеозой::Пермская; Палеозой::Каменноугольная; Paleozoic::Permian; Paleozoic::Carboniferous